Ultrahigh-temperature-resistant metal infrared reflection coating and preparation method thereof
By using sandwich structures of AgTa alloy and WZr alloy in metal infrared reflective coating, the problem of poor thermal stability at high temperature is solved, and the coordinated optimization of high infrared reflectivity and thermal stability in 700℃ environment is achieved, suitable for light The field of heat conversion and aerospace.
Patent Information
- Application Number
- CN202411626904.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-03
AI Technical Summary
The existing metal infrared reflective coatings have poor thermal stability at high temperatures, making it difficult to maintain structural stability and high infrared reflectivity at temperatures higher than 600°C, limiting their application in the fields of photothermal conversion and aerospace.
The metal infrared reflective coating adopts a sandwich structure, including a diffusion barrier layer, a metal infrared reflective layer and a diffusion barrier layer. The metal infrared reflective layer is an AgTa alloy film and a WZr alloy film. The Ag and The stability and optical properties of W are matched to form a high temperature resistant coating.
The coordinated optimization of high thermal stability and optical performance with maintaining more than 95% infrared reflectivity in an environment of 700°C is achieved. It is suitable for selective absorption coatings to reduce infrared emissivity, with simple process, low cost and good repeatability.
Smart Images

Figure CN119243088A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical films, and in particular to an ultra-high temperature resistant metal infrared reflective coating and a preparation method thereof. Background Art
[0002] Infrared reflective coating is a surface coating with high reflectivity in the infrared band. It can achieve high reflectivity and low emission in the infrared band, and can effectively reduce surface thermal emissivity and thermal radiation loss. It is widely used in solar energy conversion, construction, aerospace and other fields, and has received more and more attention in recent years. However, the commonly used infrared reflective coatings usually use high melting point materials such as Mo, W or TiN. Their infrared reflective performance is reduced due to the intensified electron-phonon interaction of metals at high temperatures, or their own infrared reflective ability is poor. These greatly limit the application of materials in the fields of photothermal conversion, aerospace, etc., so there is an urgent need to obtain a material with both high thermal stability and high infrared reflective performance.
[0003] Since the beginning of the 21st century, people have conducted extensive and in-depth research on infrared reflective coatings, so that they can maintain high infrared reflectivity without attenuation of optical properties under high temperature working conditions (>600 ºC). At present, the coating is usually based on metal films. Publication No. CN109373619A discloses a selective absorption coating with an infrared reflective layer of Al, Cu, Mo, W, Cr, Co or Pt film, which can maintain an emissivity below 0.17 after annealing in a vacuum at 500 ºC for 500 hours. However, these pure metal films are often unstable and easily oxidized. At higher temperatures, they tend to agglomerate, resulting in coarsening of the grains of the nanofilm, leading to performance degradation.
[0004] Therefore, in order to obtain metal infrared reflective coatings that can withstand high temperatures, researchers have used a microalloyed metal atom stabilization strategy to improve the thermal stability of these metal infrared reflective coatings. In previous studies, Al was introduced into the Ag film, and the diffusion of Ag was inhibited by forming an Al2O3 passivation layer on the AgAl surface at high temperatures. It was used as an infrared reflective layer for the construction of photothermal coatings, and it was stable for a long time (>1000 h) at 500 ºC (JH Gao, XY Wang, B.Yang, and et al. Plasmonic AgAl bimetallic alloy nanoparticles / Al2O3nanocermet thin films with robust thermal stability for solar thermalapplications. Advanced Materials Interfaces, 2016, 3:1600248). Specifically, this method thermally drives Al atoms to diffuse outward from the AgAl bimetallic alloy nanoparticles, and because Al is easily oxidized, an armor layer is formed on the surface, which can effectively form a barrier to prevent Ag from diffusing in the layer and inhibit the migration of Ag atoms. Therefore, microalloying is an effective way to improve the thermal stability of metal films while maintaining high reflective performance.
[0005] Up to now, it is still a major challenge to achieve metal infrared reflective coatings at higher temperatures (>600℃) while maintaining long-term structural stability and high infrared reflectivity. The thermal stability problem of its nanoparticle system at high temperatures (>600℃) has not been effectively solved. Therefore, obtaining a metal infrared reflective layer that can be used stably at higher temperatures is still a major problem for us at this stage. Summary of the invention
[0006] In order to solve the problem of poor high-temperature stability of reflective coatings, the present invention provides an ultra-high temperature resistant metal infrared reflective coating, which has thermal stability at higher temperatures (>600°C) and high infrared reflective performance, is suitable for various selective absorption coatings to reduce their infrared emissivity, and has a simple preparation process and good repeatability.
[0007] To achieve the above object, the technical solution adopted by the present invention is: An ultra-high temperature resistant metal infrared reflective coating, the metal infrared reflective coating comprising a diffusion barrier layer, a metal infrared reflective layer and a diffusion barrier layer in order from a substrate outward; The metal infrared reflection layer is an AgTa alloy film, and the diffusion barrier layer is a WZr alloy film.
[0008] likeFigure 1 As shown, the coating of the sandwich structure is designed in the present invention, and the high temperature resistant metal infrared reflective coating needs to improve the comprehensive optical performance and thermal stability, so the mutual matching between different film layers is very important. On the one hand, Ag has excellent infrared reflection ability and is one of the most promising low emissivity metals. The Ag-based alloy is selected as the infrared reflective layer, which has a very high reflectivity in the near-infrared band range, and the reflectivity at the infrared band wavelength can reach more than 98%. Therefore, the use of Ag-based alloy as the infrared reflective layer can more significantly improve the infrared reflectivity of the system; at the same time, the introduction of Ta in the metal Ag film can inhibit the diffusion and agglomeration of Ag nanoparticles at high temperatures; on the other hand, the upper and lower barrier layers can inhibit the possibility of Ag nanoparticles diffusing and evaporating outward at high temperatures, and the Ag nanoparticle system is stabilized by the superposition of the two, so that it still has high infrared reflectivity at high temperatures.
[0009] The present invention is based on the idea of enhancing the thermal stability of nanometals by microalloying, and adopts the idea of improving the thermal stability of its microstructure by heat diffusion-driven segregation and passivation in the AgTa bimetallic nanosystem. Ta is selected as the doping metal because Ta has low segregation energy in the Ag alloy and is more likely to segregate to the grain boundary, which can constitute a resistance to grain boundary migration and can more effectively improve the stability of Ag. The introduction of Zr is on the one hand to improve the thermal stability of the W nanostructure. Compared with other metals, Zr has low segregation energy in the W alloy and is more likely to segregate to the grain boundary, which can more effectively improve the stability of W. On the other hand, it is to regulate the optical constants of W so that it can better optically match with the AgTa film and minimize the loss of optical performance.
[0010] The atomic percentage of Ta in the metal infrared reflective layer is 0.5 at%-3 at%; the addition of Ta in Ag can improve stability, but will affect the reflectivity of the film. Excessive addition will cause performance loss of the entire reflective coating. Preferably, the atomic percentage of Ta in the metal infrared reflective layer is 1 at%-2.4 at%; The atomic percentage of Zr in the diffusion barrier layer is 2 at%-8 at%. The volume fraction of metal Zr in the diffusion barrier layer and the thickness of the AgTa layer film need to match each other. By introducing Zr to regulate the optical properties of W to better match the AgTa alloy layer film, the optical properties and thermal stability of the high temperature resistant metal infrared reflective layer can be synergistically optimized. Preferably, the atomic percentage of Zr in the diffusion barrier layer is 3 at%-7 at%.
[0011] The thickness of the metal infrared reflective layer is above 100nm, and a higher thickness can achieve effective infrared reflectivity. The thickness of the diffusion barrier layer is 5-25nm. The metal diffusion barrier layer mainly inhibits the possibility of Ag nanoparticles diffusing and evaporating outward at high temperature. If the thickness is too thin, the inhibition effect is not obvious. If the thickness is too thick, it will in turn affect the overall reflection spectrum and sometimes reduce the infrared reflection performance of the coating.
[0012] The thickness of the diffusion barrier layer close to the substrate is 10-20nm, and the thickness of the diffusion barrier layer far from the substrate is 5-15nm. Below this thickness range, the inhibition of Ag nanoparticles from diffusing outward and evaporating at high temperature is not obvious, and above this thickness range, the overall reflection spectrum is affected, resulting in a decrease in reflection performance.
[0013] The present invention also provides a method for preparing the ultra-high temperature resistant metal infrared reflective coating, comprising the steps of: Step 1, selecting metal W and Zr as co-sputtering targets, with W located at a DC target position and Zr located at a RF target position, performing multi-target magnetron sputtering on a pretreated substrate, and applying plasma bombardment assistance to obtain a diffusion barrier layer; Step 2, selecting metal Ag and Ta as co-sputtering targets, with Ag located at a DC target position and Ta located at a RF target position, performing multi-target magnetron sputtering on the diffusion barrier layer, applying plasma bombardment assistance, and obtaining a metal infrared reflection layer; Step 3, selecting metal W and Zr as co-sputtering targets, with W located at the DC target position and Zr located at the RF target position, performing multi-target magnetron sputtering on the metal infrared reflective layer, applying plasma bombardment assistance, to obtain the metal infrared reflective coating.
[0014] The gas pressure during multi-target magnetron sputtering is 0.2-0.3Pa.
[0015] The substrate includes any one of silicon dioxide, stainless steel, silicon wafer and thermal silicon.
[0016] The pretreatment method includes ultrasonic cleaning of the substrate using acetone, alcohol and deionized water in sequence, followed by heating desorption and plasma sputtering cleaning.
[0017] The power used for metal targets Ag and W is 1.5-4 W / cm 2 .
[0018] The power range of the metal target Ta is 0-0.8 W / cm 2 ; The power range of metal target Zr is 0-0.5W / cm 2 .
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts magnetron sputtering to directly deposit the WZr diffusion barrier layer and the AgTa infrared reflection layer, which not only has simple process, low cost, convenient parameter control and good repeatability, but also has a uniform coating structure and stable properties, which is very conducive to large-scale production.
[0020] (2) From the perspective of optical performance, the metallic infrared reflective coating of the present invention has high infrared reflective performance, and the reflectivity in the infrared band can reach more than 95%.
[0021] (3) From the perspective of thermal stability, the metallic infrared reflective coating of the present invention has high thermal stability. After annealing at 700 °C, the reflectivity in the infrared band can still remain above 95%, and the nanostructure remains stable after annealing. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic cross-sectional view of the metal infrared reflective coating of the present invention.
[0023] Figure 2 This is the optical reflection spectrum of the AgTa film with different Ta doping amounts in Example 1.
[0024] Figure 3 XRD spectra of AgTa films with different Ta doping amounts in Example 1.
[0025] Figure 4 The optical reflection spectra of the metal infrared reflective coating of the top WZr diffusion barrier layer simulated with different Zr doping amounts in Example 2.
[0026] Figure 5 The optical reflection spectra of the metal infrared reflective coating with top WZr diffusion barrier layers of different thicknesses simulated in Example 2.
[0027] Figure 6 This is the optical reflection spectrum of the infrared reflection coating with Ag as the main infrared reflection layer prepared in Example 3 before and after heat treatment.
[0028] Figure 7 Optical reflection spectra of the infrared reflection coating prepared in Example 3 with AgTa (Ta atomic ratio of 1.14 at%) as the main infrared reflection layer before and after heat treatment.
[0029] Figure 8 Optical reflection spectra of the infrared reflection coating prepared in Example 3 with AgTa (Ta atomic ratio of 2.40 at%) as the main infrared reflection layer before and after heat treatment.
[0030] Fig. 9 This is the optical reflection spectrum of the infrared reflective coating with W as the main diffusion barrier layer prepared in Example 4 before and after heat treatment.
[0031] Fig.10 Optical reflection spectra of the infrared reflective coating prepared in Example 4 with WZr (Zr atomic ratio of 3.34 at%) as the main diffusion barrier layer before and after heat treatment.
[0032] Fig.11 Optical reflection spectra of the infrared reflective coating prepared in Example 4 with WZr (Zr atomic ratio of 7.02 at%) as the main diffusion barrier layer before and after heat treatment. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0034] The raw materials used in the following specific embodiments are all purchased from the market.
[0035] Example 1 Step 1: First, clean the substrate by ultrasonically cleaning the quartz plate with acetone, ethanol and deionized water for 15 minutes to remove surface contaminants; then, dry the cleaned substrate with nitrogen and fix it on the substrate tray; load the tray into the magnetron sputtering equipment preparation room, and evacuate the vacuum gauge to 5×10 using a mechanical pump and a molecular pump. -4 Pa, the tray is transferred into the deposition chamber.
[0036] Step 2, after entering the deposition chamber, open the Ar gas line, and introduce Ar gas to keep the pressure in the deposition chamber at 0.4 Pa, turn on the RF sputtering to clean the Ta target and the DC power supply to clean the Ag target for 30 minutes, and clean it 3 times in total.
[0037] Step 3: After cleaning, use the molecular pump in the deposition chamber to pump the pressure in the chamber to 1×10 -4 Then, Ar gas was introduced to adjust the pressure in the deposition chamber to 0.2 Pa. At this time, the DC drive power of the Ag target was turned on and its sputtering power was adjusted to 2.5 W / cm 2 By adjusting the power of the Ta RF target, AgTa alloy films doped with different Ta atomic ratios were obtained. The deposition time was 11 min, and infrared reflective coatings with Ag as the main component were obtained, with a thickness of about 100 nm. After the time was up, the Ag target, Ta target and their corresponding bias drive power were turned off to obtain metal infrared reflective coatings with different Ta contents.
[0038] The reflectance spectra of AgTa films with different Ta doping amounts in the 2.5-20 μm band were measured by Fourier transform infrared spectroscopy. Figure 2 As shown, it can be seen that with the increase of Ta content, the reflectivity of AgTa film decreases monotonically; when the Ta content reaches 3at%, its reflectivity in the 2.5-20 μm band is generally lower than 95%, which has a great impact on its optical properties.
[0039] Generally speaking, the reliable physical properties of thin films are well coupled with the stability of their phase structures. Figure 3 The XRD patterns of AgTa films with different Ta doping amounts are given. It can be clearly seen that all samples have the strongest peak at 38.114°, and the peak intensity decreases monotonically with the increase of Ta doping amount. The average particle size determined by Scherrer's formula also decreases monotonically, indicating that Ta doping affects the growth and orientation of Ag and can inhibit the nucleation growth of Ag. However, the inhibitory effect of Ta doping at too low a content is limited. When the Ta content is lower than 1 at%, the peak intensity is still strong compared with the other samples.
[0040] Therefore, the preferred atomic percentage of Ta atoms in the AgTa metal infrared reflection layer is 1 at% to 2.4 at%.
[0041] Example 2 Step 1: First, clean the substrate by ultrasonically cleaning the quartz plate with acetone, ethanol and deionized water for 15 minutes to remove surface contaminants; then, dry the cleaned substrate with nitrogen and fix it on the substrate tray; load the tray into the magnetron sputtering equipment preparation room, and evacuate the vacuum gauge to 5×10 using a mechanical pump and a molecular pump. -4 Pa, the tray is introduced into the deposition chamber.
[0042] Step 2, after entering the deposition chamber, open the Ar gas line, and introduce Ar gas to keep the pressure in the deposition chamber at 0.4 Pa, turn on the RF sputtering to clean the Zr target and the DC power supply to clean the W target for 30 minutes, and clean it 3 times in total.
[0043] Step 3: After cleaning, use the molecular pump in the deposition chamber to pump the pressure in the chamber to 1×10 -4 Then, Ar gas was introduced to adjust the pressure in the deposition chamber to 0.2 Pa. At this time, the DC drive power of the W target was turned on and its sputtering power was adjusted to 2.5 W / cm 2 By adjusting the Zr RF target power, WZr alloy films doped with different Zr atomic ratios were obtained. The deposition time was 2.5 min and the thickness was about 5 nm. After the time was up, the W target, Zr target and their corresponding bias driving power supplies were turned off to obtain diffusion barrier layers with different Zr doping amounts and different WZr film thicknesses.
[0044] The optical constants of WZr films with different Zr doping amounts in the 190-1700 nm band were obtained by ellipsometry fitting, and then the effects of different Zr doping amounts and different WZr film thicknesses in the WZr / AgTa / WZr structure on its optical properties were simulated by macleod.
[0045] like Figure 4 As the Zr content increases, the reflectivity of the simulated film decreases monotonically, but the effect is not significant, especially near the infrared band. Therefore, the introduction of a small amount of Zr has almost no effect on the overall reflectivity. Figure 5 As shown in the figure, with the increase of the thickness of the WZr protective layer, the reflectivity of the simulated film decreases monotonically, and when the thickness exceeds 15 nm, it has a significant impact on the reflectivity of the entire coating and is not suitable for use; since the reflectivity of metals in the infrared band tends to be stable, it can also be inferred that the introduction of a small amount of Zr has almost no effect on the overall reflectivity in the infrared band. When the thickness exceeds 15 nm, it has a significant impact on the reflectivity of the entire coating in the infrared band. Therefore, the preferred atomic percentage of Zr atoms in the WZr diffusion barrier layer is 3 at% to 7 at%, and the preferred thickness range of the WZr diffusion barrier layer is 5 to 15 nm.
[0046] Example 3 Step 1: First, clean the substrate by ultrasonically cleaning the quartz plate with acetone, ethanol and deionized water for 15 minutes to remove surface contaminants; then, dry the cleaned substrate with nitrogen and fix it on the substrate tray; load the tray into the magnetron sputtering equipment preparation room, and evacuate the vacuum gauge to 5×10 using a mechanical pump and a molecular pump. -4 Pa, the tray is introduced into the deposition chamber.
[0047] Step 2, after entering the deposition chamber, open the Ar gas line, and introduce Ar gas to keep the pressure in the deposition chamber at 0.4 Pa, start RF sputtering to clean the Ta target and Zr target for 30 minutes, and use DC power to clean the Ag target and W target for 30 minutes.
[0048] Step 3: After cleaning, use the molecular pump in the deposition chamber to pump the pressure in the chamber to 1×10 -4 Then, Ar gas was introduced to adjust the pressure in the deposition chamber to 0.2 Pa. At this time, the DC sputtering power of the W target was adjusted to 2.5 W / cm 2 The RF sputtering power of Zr target is 0.25 W / cm 2 After the discharge process of the entire deposition chamber is stable, the baffle on the target surface is unscrewed to start sputtering. The sputtering time is 10 min. After the time is up, the W target, Zr target and their corresponding bias drive power supplies are turned off; Step 4: Turn on the DC drive power supply of the Ag target and adjust its power to 2.5 W / cm 2 At the same time, another Ta target RF driving power supply is turned on, and the AgTa alloy film doped with different Ta atomic ratios is obtained by adjusting the Ta RF target power. The deposition time is 11 min and the thickness is about 100 nm. After the time is up, the Ag target, Ta target and their corresponding bias driving power supplies are turned off. Step 5: Turn on the DC drive power of the W target again and adjust its power to 2.5 W / cm 2 , and another Zr target RF drive power supply with a power of 0.25 W / cm 2 , the deposition time is 2.5 min, and a batch of high-temperature resistant metal infrared reflective coatings doped with different Ta atomic ratios can be obtained. After the time is over, turn off the W target, Zr target and their corresponding bias driving power supply.
[0049] When comparing the thermal stability of the coating at high temperatures, in order to prevent Ag from evaporating at high temperatures and contaminating the instrument and subsequent samples from being bombarded by high-energy ions during FIB processing, a 40 nm SiO2 layer was plated on the sample surface by magnetron sputtering before annealing. Specifically, the DC drive power of the SiO2 target was turned on and the power was adjusted to 4 W / cm 2 , the deposition time is 75 min, and a 40 nm thick SiO2 can be plated on the sample surface to obtain a structure such as Figure 1 As shown, high temperature resistant metal infrared reflective coatings with different Ta doping amounts in the intermediate metal infrared reflective layer.
[0050] The samples prepared above were placed in a tubular vacuum annealing furnace for high vacuum annealing at 700 °C. Figure 6-Figure 8 The infrared reflection spectra of the prepared coating before and after annealing at 700 ℃ are given. Figure 6 Optical reflection spectra of pure Ag high-temperature resistant metal infrared reflection coating before and after heat treatment as the intermediate metal infrared reflection layer. Figure 7 Optical reflection spectra of the high-temperature resistant metal infrared reflection coating with a Ta atomic ratio of 1.14 at% in the intermediate metal infrared reflection layer before and after heat treatment. Figure 8 This is the optical reflection spectrum of the high-temperature resistant metal infrared reflection coating with a Ta atomic ratio of 2.40 at% in the intermediate metal infrared reflection layer before and after heat treatment.
[0051] It can be seen that after the coating with pure Ag as the main reflective layer undergoes high-temperature annealing at 700 °C, its reflectivity in the infrared band decreases monotonically with the extension of annealing time; and with the introduction of Ta, the reflectivity of the coating in the infrared band increases after the initial annealing at 700 °C and then remains stable, and the more Ta doping, the more stable it is.
[0052] Example 4 Step 1: First, clean the substrate by ultrasonically cleaning the quartz plate with acetone, ethanol and deionized water for 15 minutes to remove surface contaminants; then, dry the cleaned substrate with nitrogen and fix it on the substrate tray; load the tray into the magnetron sputtering equipment preparation room, and evacuate the vacuum gauge to 5×10 using a mechanical pump and a molecular pump. -4 Pa, the tray is introduced into the deposition chamber.
[0053] Step 2, after entering the deposition chamber, open the Ar gas line, and introduce Ar gas to keep the pressure in the deposition chamber at 0.4 Pa, start RF sputtering to clean the Ta target and Zr target for 30 minutes, and use DC power to clean the Ag target and W target for 30 minutes.
[0054] Step 3: After cleaning, use the molecular pump in the deposition chamber to pump the pressure in the chamber to 1×10 -4 Then, Ar gas was introduced to adjust the pressure in the deposition chamber to 0.2 Pa. At this time, the DC sputtering power of the W target was adjusted to 2.5 W / cm 2 By adjusting the power of the Zr RF target, WZr alloy films doped with different Zr atomic ratios were obtained. After the discharge process in the entire deposition chamber was stable, the baffle on the target surface was unscrewed and sputtering began. The sputtering time was 10 min. After the time was up, the W target, Zr target and their corresponding bias driving power supplies were turned off to obtain a diffusion barrier layer. Step 4: Turn on the DC drive power supply of the Ag target and adjust its power to 2.5 W / cm 2 At the same time, turn on the other Ta target RF drive power and set the Ta target power to 0.45 W / cm 2 The deposition time is 11 min, and an AgTa infrared reflective coating with a Ta atomic ratio of about 2.4 at% and a thickness of about 100 nm is obtained. After the time is up, the Ag target, the Ta target and their corresponding bias driving power supplies are turned off to obtain a metal infrared reflective layer on the diffusion barrier layer. Step 5: Turn on the DC drive power of the W target again and adjust its power to 2.5 W / cm 2 , and another Zr target RF driving power supply, and set different Zr RF target powers. The deposition time is 2.5 min, and a batch of high-temperature resistant metal infrared reflective coatings with diffusion barrier layers with different Zr doping amounts can be obtained. After the time is over, turn off the W target, Zr target and their corresponding bias driving power supplies.
[0055] The samples prepared above were placed in a tubular vacuum annealing furnace for high vacuum annealing at 700 °C. Figure 9-11The infrared reflection spectra of the prepared high temperature resistant metal infrared reflection coatings with different diffusion barrier layers before and after annealing at 700 ℃ are given. Fig. 9 Optical reflection spectra of the infrared reflective coating prepared in Example 4 with W as the main diffusion barrier layer and without Zr doping before and after heat treatment. Fig.10 Optical reflection spectra of the infrared reflective coating prepared in Example 4 with WZr (Zr atomic ratio of 3.34 at%) as the main diffusion barrier layer before and after heat treatment. Fig.11 Optical reflection spectra of the infrared reflective coating prepared in Example 4 with WZr (Zr atomic ratio of 7.02 at %) as the main diffusion barrier layer before and after heat treatment.
[0056] It can be seen that compared with the sample with pure W as the diffusion barrier layer, the sample with WZr as the diffusion barrier layer has smaller changes in optical properties after annealing and better optical stability at 700 °C.
Claims
1. A metal infrared reflective coating resistant to ultra-high temperatures, characterized in that: The metal infrared reflective coating comprises, from the substrate outwards, a diffusion barrier layer, a metal infrared reflective layer and a diffusion barrier layer; The metal infrared reflection layer is an AgTa alloy film, and the diffusion barrier layer is a WZr alloy film.
2. The ultra-high temperature resistant metal infrared reflective coating according to claim 1, characterized in that: The atomic percentage of Ta in the metal infrared reflection layer is 0.5 at%-3 at%; the atomic percentage of Zr in the diffusion barrier layer is 2 at%-8 at%.
3. The ultra-high temperature resistant metal infrared reflective coating according to claim 1, characterized in that: The atomic percentage of Ta in the metal infrared reflection layer is 1 at%-2.4 at%; the atomic percentage of Zr in the diffusion barrier layer is 3 at%-7 at%.
4. The ultrahigh temperature resistant metal infrared reflective coating according to claim 1, characterized in that: The thickness of the metal infrared reflection layer is above 100 nm.
5. The ultra-high temperature resistant metal infrared reflective coating according to claim 1, characterized in that: The thickness of the diffusion barrier layer close to the substrate is 10-20 nm, and the thickness of the diffusion barrier layer far from the substrate is 5-15 nm.
6. The method for preparing the ultrahigh temperature resistant metal infrared reflective coating according to any one of claims 1 to 5, characterized in that: Includes steps: Step 1, selecting metal W and Zr as co-sputtering targets, with W located at a DC target position and Zr located at a RF target position, performing multi-target magnetron sputtering on a pretreated substrate, and applying plasma bombardment assistance to obtain a diffusion barrier layer; Step 2, selecting metal Ag and Ta as co-sputtering targets, with Ag located at a DC target position and Ta located at a RF target position, performing multi-target magnetron sputtering on the diffusion barrier layer, applying plasma bombardment assistance, and obtaining a metal infrared reflection layer; Step 3, selecting metal W and Zr as co-sputtering targets, with W located at the DC target position and Zr located at the RF target position, performing multi-target magnetron sputtering on the metal infrared reflective layer, applying plasma bombardment assistance, to obtain the metal infrared reflective coating.
7. The method for preparing the ultrahigh temperature resistant metal infrared reflective coating according to claim 6, characterized in that: The gas pressure during multi-target magnetron sputtering is 0.2-0.3 Pa.
8. The method for preparing the ultrahigh temperature resistant metal infrared reflective coating according to claim 6, characterized in that: The substrate comprises any one of silicon dioxide, stainless steel, silicon wafer and thermal silicon; The pretreatment method includes ultrasonic cleaning of the substrate using acetone, alcohol and deionized water in sequence, followed by heating desorption and plasma sputtering cleaning.
9. The method for preparing the ultrahigh temperature resistant metal infrared reflective coating according to claim 6, characterized in that: The power used for metal targets Ag and W is 1.5-4 W / cm 2 .
10. The method for preparing the ultrahigh temperature resistant metal infrared reflective coating according to claim 6, characterized in that: The power range of the metal target Ta is 0-0.8 W / cm 2 ; The power range of the metal target Zr is 0-0.5 W / cm 2 .
